Subjective Dry Eye Symptoms in Pregnant Women–A SPEED Survey - Divya Anantharaman; Aiswaryah Radhakrishnan; Vidhyalakshmi Anantharaman (Journal of Pregnancy)
Aim. Multisystemic physiological changes in pregnancy can result in tear film and refractive changes in the eye. We report dry eye prevalence in pregnant women using Standard Patient Evaluation of Eye Dryness (SPEED) questionnaire. Methods. The SPEED questionnaire was self-administered cross-sectionally to 428 pregnant women (mean age: 26.8±4.4 years) with clinically confirmed pregnancy from two obstetric clinics in Chennai, India. Subjects with predisposing risk factors for dry eye were excluded from the study. Subjects were categorized as normal, moderate, and severe dry eye based on the SPEED score. Results. Among the women, 48.5% of the subjects had symptoms like dryness, grittiness or scratchiness, soreness or irritation, burning or watering, or eye fatigue. About 2.3% had moderate dry eye according to SPEED questionnaire criteria. Eye fatigue was the most reported symptom and was present in 76.4% of women. The symptom frequency score and severity score had a strong and significant correlation (r=0.95, P<.001). No significant correlation was noted among SPEED score vs age (r=−0.02, P>.05). No significant correlation was found between symptoms of dry eye and gravidity (ρ=−0.006, P>.05) and trimester (ρ=0.38, P>.05). Binary logistic regression showed that only occupational status and systemic condition was significantly associated with dry eye symptoms. Conclusion. About half the pregnant women at the visit reported having one or more dry eye-related symptoms. As per the composite SPEED questionnaire score, dry eye was not prevalent among pregnant women irrespective of their age, gravidity, and the trimester, but we found a majority of pregnant women reported to have experienced dry eye-related symptoms, though tolerable. Awareness about dry eye during pregnancy will improve eye care seeking behaviour in pregnant women.